Geotechnical characterization of circulating fluidized bed (CFB) fly ash - Canlobo, Kim Aeron E.; Santos, Jon Ross V.
This is a pioneering study to characterize and identify potential engineering applications of Circulating Fluidized Bed (CFB) fly ash. This study focuses on the specific gravity, particle size distribution, Atterberg limits, permeability, and compaction of CFB fly ash. The fly ashes were taken from the United Pulp and Paper Corporation in Calumpit, Bulacan and from the Cebu Energy Development Corporation in Toledo City, Cebu. These two samples have undergone specific gravity test using water pycnometer, sieve and hydrometer analysis, plastic and liquid limit test, falling head test, and standard proctor test in accordance with the American Standard for Testing and Materials. After testing, they were characterized and the results showed that the specific gravities of the samples are relatively low, ranging from 2.43 to 2.50 with an average of 2.47. The samples are both poorly graded with average particle sizes of 15% sand, 75% silt, and 10% clay for Bulacan CFB fly ash and 22% sand, 69% silt, and 9% clay for Cebu CFB fly ash. In addition, the samples are non-plastic with plasticity index equal to zero. The liquid limits are high ranging from 30% to 51%. The permeability of Bulacan CFB fly ash is low ranging from 3.42 x 10-5 to 3.51 x 10-5 cm/s, whereas the permeability of Cebu CFB fly ash is also low ranging from 8.56 x 10-4 to 8.92 x 10-4 cm/s. The samples have high optimum moisture contents ranging from 58% to 61% and low maximum dry densities ranging from 8.82 to 9.14 kN/m3. Hence, the possible engineering applications for the CFB fly ash are the following: landfill cover or hydraulic barrier, base/subbase material, flowable fills and agricultural limestone substitute.